Study of kinetics of plastic deformation propagation in welded joints with 10G2FB steel after welding in a shielding gases environment - Саєнко, Владислав Олександрович (Харківський національний автомобільно-дорожній університет, 2023)
The object of research is kinetics dissemination plastic deformation _ welded joints of low-carbon microalloyed steel 10G2FB in the environment of protective gases. The purpose of the work is to investigate relationship between external deformation and corresponding kinetics of propagation of plastic deformation of welded joints of low-carbon microalloyed steel 10G2FB in the environment of shielding gases. Research methods and equipment: tests on stretching research structures on electron raster microscope, semi-quantitative metallographic analysis. The structure of the joint after welding in the environment of shielding gases was studied. The relationship between the external load and the general deformation is analyzed. The general characteristics of the welded joint have been developed with points vision distribution load. Researched dissemination of plastic deformation in the zones of the welded joint of steel 10G2FB after welding in an environment of shielding gases. The general features of the nucleation of destruction in structure of steel 10G2FB after welding in environment of protective gases. Considered issues of labor protection and safety in emergency situations when working in the laboratory.
Keywords: welding; zone melting; zone thermal influence; weld seam; plastic deformation